Human Capital Development as an Element of Financial Management in National Education Systems - SLEPOV, Vladimir Alexandrovich; RODENKOVA, Tatyana Nikolaevna; KOSOV, Mikhail Evgenievich; GRISHIN, Alexey Igorevich (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
In recent decades, human capital has become a key element in the development of countries all over the world. The consumer demand for complex products and services (the reflection of human capital in the field of consumption) can enhance the increase in financial and economic indicators. Accordingly, education in the modern economy should not be considered as a field that requires high costs, but rather as an investment field that determines the scale of economic growth. Meanwhile, the policy of financial support of higher education in Russia is still largely focused not on the contribution to the economic and social development of the country, but the internal problems of the system, relying on the notion of education as a sphere of social obligations. In this regard, the transformation of conceptual approaches to the financial management of universities, involving the improvement of the methods used and the development of new methods and models, is of particular relevance. The study aims to develop the methods and models of university financial management given the modern conditions of financial support for educational institutions of higher education for the development of human capital. The research methods include a review of the scientific literature in this field, synthesis, and analysis of the information received, as well as comparison, formalization, and specification. The study identifies modern approaches to the financial management of Russian universities by assessing existing methods and models, as well as the specifics of financing universities in the current conditions of financial support for education. Given the concept of a university as a self-learning organization within the framework of the new paradigm of financial management and human capital development, a system model of financial decision making should be used.